Kedudukan Hak Konsumen dalam Memperoleh Informasi yang Jujur terhadap Produk Makanan dan Minuman - Bambang Satriya (University of Merdeka Malang, 2019)
Consumers have several rights which are arranged in Indonesia’s rules of law. One of the rights is the right to honest information towards the products which are going to be used or consumed. This is a juridical normative research implementing rules of law and conceptional approach whose legal materials are primary, secondary, tertiary materials. Results of the research show that juridical protection as an existence of consumers’ rights in obtaining honest information towards particular food and beverages they should have had is still an unreachable right. This occurs because several findings indicate that many producers or businesses in several levels including local, national, and global violate juridical norms. Consumers whose positions are potential and strong juridically could still become theinjured party or become the target to reach and fulfil the profit as much as possible. As a result, fromthis violated information rights, other consumers’ rights such as health and safety are automatically neglected. In this domain, consumers become the casualties or become the object of cumulative human rights violation.How to cite item : Satriya, B. (2019). Kedudukan Hak Konsumen dalam Memperoleh Informasi yang Jujur terhadap Produk Makanan dan Minuman. Jurnal Cakrawala Hukum, 10(2), 137-145. doi:https://doi.org/10.26905/idjch.v10i2.3369